2021
DOI: 10.1021/acs.orglett.1c03714
|View full text |Cite
|
Sign up to set email alerts
|

Electron-Catalyzed Aminocarbonylation: Synthesis of α,β-Unsaturated Amides from Alkenyl Iodides, CO, and Amines

Abstract: Aminocarbonylation of alkenyl iodides with CO and amines proceeded under heating to produce α,β-unsaturated amides in good yields (23 examples, 71% average yield). This catalyst-free method exhibited good functional-group tolerance, and open a straightforward access to functionalized acrylamides, as illustrated by the synthesis of Ilepcimide. A hybrid radical/ionic mechanism involving chain electron transfer is proposed for this transformation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Encouraged by the formation of variable amounts of single carbonylation product amide 4aa in the double carbonylation processes, we proceeded to identify suitable conditions to improve the selectivity of single carbonylation for the synthesis of amide 4aa . In the context of photochemical synthesis, many redox or simple electron-transfer steps that are estimated to be endergonic by simple comparison of redox potentials become exergonic when additives were added. , Also, drawing inspiration from the N -philic mode of acyl radicals pioneered by Ryu, we attempted to add various amines such as bases, Lewis bases, or π-systems to tune the single carbonylation selectivity. We were pleased to discover that the addition of stoichiometric 4-dimethylaminopyridine (DMAP) (3.0 equiv) could completely reverse the product distribution to the predominant formation of single carbonylation product 4aa under otherwise identical conditions (98% yield, Figure C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Encouraged by the formation of variable amounts of single carbonylation product amide 4aa in the double carbonylation processes, we proceeded to identify suitable conditions to improve the selectivity of single carbonylation for the synthesis of amide 4aa . In the context of photochemical synthesis, many redox or simple electron-transfer steps that are estimated to be endergonic by simple comparison of redox potentials become exergonic when additives were added. , Also, drawing inspiration from the N -philic mode of acyl radicals pioneered by Ryu, we attempted to add various amines such as bases, Lewis bases, or π-systems to tune the single carbonylation selectivity. We were pleased to discover that the addition of stoichiometric 4-dimethylaminopyridine (DMAP) (3.0 equiv) could completely reverse the product distribution to the predominant formation of single carbonylation product 4aa under otherwise identical conditions (98% yield, Figure C).…”
Section: Resultsmentioning
confidence: 99%
“…The lowest unoccupied molecular orbital allowed such a radical class to act as electrophiles to react with nucleophiles, such as amines and electron-rich π-systems. For example, a range of pioneering studies by Ryu demonstrated that acyl radicals could also react as electrophilic radicals toward amines, selectively leading to various highly functionalized mono carbonylation amide products. Moreover, combined experimental and density functional theory (DFT) computational studies by the groups of Ryu and Schiesser have also disclosed that acyl radicals were able to mask as electrophiles to attack at the most nucleophilic end of NC π-systems, providing a powerful method for the synthesis of various nitrogen-containing compounds . Drawing inspiration from these works, we think the philicity-regulation strategy would probably allow the development of switchable radical carbonylation reactions.…”
Section: Introductionmentioning
confidence: 99%
“…The electron-catalyzed aminocarbonylation strategy was extended to alkenyl iodides (Scheme 9). 39 This process was found to be compatible with various amines and alkenyl iodides, and the bioactive Ilepcimide could be synthesized using this protocol. Alkenyl bromides, however, were not converted under these conditions.…”
Section: Alkenyl Radical Carbonylation Accompanied By Electron Transfermentioning
confidence: 95%
“…Like quinazoline α, β-Unsaturated amides [80] and maleimides [81] are fundamental building blocks of many biologically active compounds. Peng et al again, in the following year, synthesized α,β-unsaturated amides, and maleimides by palladium-catalyzed carbonylative divergent synthesis (Scheme 21).…”
Section: Metal Carbonyl As Co Sourcementioning
confidence: 99%